Plantas de cobertura e umidade antecedente afetam a infiltração de água em um argissolo - Rauber, Lucas Raimundo (2023)
Despite the hydrological importance of soil water infiltration, the characterization of its variables is a field of uncertainty in hydrology. Furthermore, relationships of infiltration with cover crops, antecedent soil moisture, and measurement scales are not sufficiently understood. The objectives were: (i) to propose automatic systems for obtaining point infiltration data for infiltrometers (chapter I); (ii) study how different systems with cover crops differ in increasing soil water infiltration and controlling surface runoff (chapter II); and (iii) study the relationships of the steady state infiltration rate measured with infiltrometers (Tie) with the antecedent soil moisture, with the permeability of the surface soil, with the measurement method and with the measurement time (chapter III). The proposition of infiltrometer automation consisted of a methodological stage and technological contribution. The systems are easy to build and use pressure transducers and an open source microcontroller (Arduino). Furthermore, these systems made it possible to obtain a robust database to relate infiltration with various factors in chapter III. To achieve the second and third objectives, two experimental protocols were used, both in Argissolo Vermelho-Amarelo Distrófico abrúptico (Ultisol), in Santa Maria/RS. The first protocol consisted of monitoring precipitation and surface runoff on a plot scale (14.5 x 3 m) in the year of 2022, in which six cover conditions were analyzed: bare soil with surface crust; forage peanuts; permanent grasses; oats and turnips in winter and beans in summer; oats and vetch in winter and beans in summer; and ryegrass in winter and beans in summer. In addition, infiltration was measured with infiltrometers in each plot. The second protocol consisted of measuring point infiltration in up to 14 antecedent soil moisture conditions between 2021 and 2023, two management conditions (no-till; no-till with soil chiseling), with two methods (double ring and Cornell infiltrometer) and by time up to 48 hours. We discovered that cover crops have a great capacity to attenuate surface runoff (97%), and that the benefits were more evident in soil covered with forage peanuts than in annual crops and permanent grasses. However, the differentiation of species in increasing infiltration depends on the characteristics of precipitation events, seasonality and measurement scale. The steady infiltration rate measured with infiltrometers depends on the antecedent soil moisture, the permeability of the surface layers, the measurement method and is low affected by extending the measurement time (> 2 h). The effects of the method and surface permeability, however, decreased with increasing antecedent soil moisture. Under a nearly saturated profile, vertical infiltration is adequately characterized by infiltrometers. Therefore, the antecedent soil moisture is an important factor that affects the steady infiltration rate that requires proper consideration.